2013
DOI: 10.4028/www.scientific.net/amr.856.92
|View full text |Cite
|
Sign up to set email alerts
|

Contact Width Analysis of Corrugated Metal Gasket Based on Surface Roughness

Abstract: Contact width is important design parameter for optimizing design of new metal gasket. The contact width was found have relationship with helium leak quantity. Increasing axial force, the contact width will increase and helium leakage will decrease. This study we conducted the surface roughness evaluation of 25A-size metal gasket before and after use. The results denote the real contact width after contact with flange having different surface roughness. The real contact width for the flange having smoother sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 4 publications
0
4
0
1
Order By: Relevance
“…From the examination of each conditions of contact stress using numerical analysis which has been mentioned above it is clear that flange surface roughness give effect to the contact area and contact stress, Haruyama et al [6]. Haruyama et al [7] studied the real measurement result of contact width, area when surface roughness is considered and local contact stress have been examined through numerical analysis and the distribution of contact stress has been clarified. Then, the gap between result of contact area measurement through surface observation and the result of numerical analysis is proved to be small.…”
Section: Introductionmentioning
confidence: 99%
“…From the examination of each conditions of contact stress using numerical analysis which has been mentioned above it is clear that flange surface roughness give effect to the contact area and contact stress, Haruyama et al [6]. Haruyama et al [7] studied the real measurement result of contact width, area when surface roughness is considered and local contact stress have been examined through numerical analysis and the distribution of contact stress has been clarified. Then, the gap between result of contact area measurement through surface observation and the result of numerical analysis is proved to be small.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research [4] also simulated contact width and contact stress on CMG based on surface roughness. The contact width between the flange and the gasket increases on the flange with lower roughness values [5]. The results showed that the high surface roughness value made it difficult to prevent leakage due to the equal material hardness between gaskets and flange.…”
Section: Introductionmentioning
confidence: 93%
“…High gasket stiffness increases contact stress but complicates the cold forming process. The hard surface of the gasket in contact with the hard surface of the flange also causes a small contact width [5]. To prevent leakage, high contact stress and large contact width are required.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Bahan baru ini diharapkan memiliki performa yang serupa dengan asbestos. Beberapa peneliti telah mencoba untuk meneliti bahan baru dan beberapa peneliti lain mengembangkan sistem sealing yang baru dengan mengoptimalkan beberapa parameter perancangan untuk meningkatkan sealing performance [1][2][3][4][5][6][7]. Belum ada produk ideal yang bisa menggantikan gasket berbahan asbestos sehingga bahan yang berbeda perlu dikembangkan agar sesuai dengan berbagai aplikasinya.…”
Section: Pendahuluanunclassified